Playful Strategies in Print Advertising - Karels, Alysa; de la Hera, Teresa (Eludamos: Journal for Computer Game Culture, 2021)
The fact that people are increasingly eager to seek out playful experiences in their everyday lives is part of a trend known as the ludification of culture. Scholars find that, in a time characterized by information overload, consumers are open and drawn to media products that offer entertainment through playful interaction. Meanwhile, the advertising industry is faced with the quandary of how to stand out and attract consumers’ fleeting attention in a landscape that has become highly competitive. Print advertising in particular faces a budget decline and has to compete with digital advertising forms that know richer affordances to appeal to consumers’ attention. For this reason, this article explores how print advertising uses playful strategies in order to stand out from the crowd and appease the demand to provide entertaining interaction for consumers. In doing so, the article focuses on the following research question: How do advertisers make use of playful communication strategies in print advertisements to stand out in the contemporary attention economy? To gain a comprehensive answer to this research question, a qualitative approach was taken. A thematic analysis of print advertisements was conducted, going through multiple rounds of coding that eventually resulted in the emergence of three central themes of playful strategies: (1) the use of playful visual design that is meant to instill a playful mindset; (2) the use of strategies based on a pleasurable interactive experiential logic; (3) the liberation of unspoken topics of a dark, solemn, and negative nature in a playful way. This study identifies playful aesthetics and their capacity for interactivity, resembling that of games, in static media forms such as print advertising; moreover, it identifies how playfulness can be used as a mode of production (playification) for the advertising industry as part of the creative industries. The conclusions and implications drawn from this article are thus theoretically and practically impactful. Regarding the former, contributions to an understanding of aesthetic interactivity and negative pleasurable experiences are made, and a need for further inquiry in playification is identified and encouraged. Regarding the latter, the benefit for advertisers to use playful print advertising strategies in their marketing mix is illuminated and ethical concerns regarding the persuasion of the strategies are expressed. The article closes by pointing out directions for future research.